Sophie Arnoux’s beginning in the world of opera (1757-1760): pictures of the “singing actress” and her repertory - Raphaëlle (MUSURGIA, 2021)
At the moment when the theatric press appears and when L’Avant-Coureur and the Affiches, Annonces et Avis divers enter in competition with the traditional Mercure de France, an image of the opera singer is progressively built, all together actress, musician, public person and embodiment of a character. What is the part of the voice in the singer’s moving acting? What are the words to qualify the sound phenomenon of vocality? What collective image of the woman on the stage is produced? Those are the questions that will be considered through a study of the accounts of the first acting years (1757-1753) of Sophie Arnoux, the last great ramist singer.